Model Empat Pilar Inovasi dalam Sinergitas Kurikulum Pesantren dan Perguruan Tinggi: Studi Kasus Pesantren Luhur Sabilussalam - Moh. Iqbal Maulidy; Babun Suharto; Wahyu Wibowo (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study is motivated by the limited familiarity of students in Islamic Higher Education Institutions (PTKI) with kitab kuning (classical Islamic texts) and the urgent need to reform pesantren systems in order to remain relevant within the dynamics of modern education. The main issue addressed is how to build effective synergy between pesantren curricula and university academic curricula to reduce this intellectual competency gap. Using a qualitative approach with a case study method at Pesantren Luhur Sabilussalam, data were collected through observation, in-depth interviews, and documentation. The findings indicate that the implementation of the “Four Pillars of Innovation” includes four main components, namely (1) the hybrid identity of mahasantri (student-santri), (2) an integrated curriculum based on the Semester Credit System (SKS), (3) hybrid pedagogy through the integration of bandongan and discussion-based learning, and (4) an egalitarian leadership ecosystem. These components have proven effective in improving academic achievement and enhancing mastery of kitab kuning. The distinctive feature of this model lies in the dual role of the kiai as both pesantren leader and university academic. In conclusion, the student pesantren model offers a strategic solution to strengthen intellectual competence and character development within Islamic higher education. This study recommends the adoption of a flexible yet structured curriculum integration model for Islamic university students more broadly.This study is motivated by the limited familiarity of students in Islamic Higher Education Institutions (PTKI) with kitab kuning (classical Islamic texts) and the urgent need to reform pesantren systems in order to remain relevant within the dynamics of modern education. The main issue addressed is how to build effective synergy between pesantren curricula and university academic curricula to reduce this intellectual competency gap. Using a qualitative approach with a case study method at Pesantren Luhur Sabilussalam, data were collected through observation, in-depth interviews, and documentation. The findings indicate that the implementation of the “Four Pillars of Innovation” includes four main components, namely (1) the hybrid identity of mahasantri (student-santri), (2) an integrated curriculum based on the Semester Credit System (SKS), (3) hybrid pedagogy through the integration of bandongan and discussion-based learning, and (4) an egalitarian leadership ecosystem. These components have proven effective in improving academic achievement and enhancing mastery of kitab kuning. The distinctive feature of this model lies in the dual role of the kiai as both pesantren leader and university academic. In conclusion, the student pesantren model offers a strategic solution to strengthen intellectual competence and character development within Islamic higher education. This study recommends the adoption of a flexible yet structured curriculum integration model for Islamic university students more broadly.